VALUES OF COLLABORATIVE-BASED ISLAMIC LEADERSHIP EDUCATION AT THE 2025 WORLD MUSLIM SCOUT JAMBOREE EVENT - Moh. Wardi; Muhammad Irfanudin Kurniawan; Khotimatul Mahbubah; Hodairiyah Hodairiyah (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
The World Muslim Scout Jamboree (WMSJ) 2025 offers a meeting space for Muslim youth from across countries that is rarely studied as an arena for the formation of global Islamic leadership. This study aims to gain a deep understanding of the experiences, values, and constructions of meaning experienced by the participants and organizers of WMSJ 2025. The research uses a qualitative, phenomenological design. Data were collected through in-depth interviews, participatory observations, and analysis of official activity documents and narratives, and then analyzed using thematic coding to capture the essence of the experience and identify recurring patterns of meaning. The findings show four categories of values that are internalized and interact simultaneously, namely: Islamic values (ukhuwah, ta'awun, morals, collective worship), scouting values (discipline, responsibility, independence, courage), civilizational values (innovation, leadership, environmental concern, ecotheology-based technological literacy), and pesantren values (Panca Jiwa Gontor as a cadre ethos). Thus, this study's findings show that normative values are translated into social practices through cross-cultural interaction in transnational scouting events.